Enhancing engagement: the transformative power of gamified learning for nursing and medical students - Abu Hassan, Norafizah; Mat Nawi, Mohd Nazim; Mat Zean, Hazaliza; Md Saad, Norlaili; Mat Yaacob, Siti Nubailah; Hisham, Balqis (Asian Journal of Research in Education and Social Sciences, 2025)
Abstract: Gamification has gained traction in education, proven to boost student motivation and engagement. Its application in statistics courses has shown promising results, enhancing performance and attitudes towards the subject. With evolving learning styles, especially among Millennials, traditional teaching methods need reassessment to ensure effective engagement and understanding of statistical concepts, which are crucial for academic success. This study aims to assess the impact of gamified experiences introduced through Statopoly, a Monopolyinspired game integrating statistics principles, on student engagement in a statistics course. Using the GAMEFULQUEST questionnaire, the study explores the effects of six key gamified experience factors on student engagement, considering cognitive and affective dimensions. Surveys were conducted with 111 students and engagement was assessed through quantitative methods. The findings reveal significant differences between Nursing and Medical students across four dimensions of the gamified learning experiences, as well as significant differences in the impact of gamification on student engagement. The result also shows a strong positive correlation between gamified learning experiences and student engagement. These outcomes underscore the promising role of gamification as a catalyst for innovation in statistics education.